Insect pheromones : the sex pheromone of Nudaurelia cytherea cytherea Fabr. : (Lepidoptera : Saturniidae) - Henderson, Howard Edward (Department of Chemistry, 2015)
Studies leading to the isolation, identification and synthesis of the sex pheromone from the female pine tree emperor moth Nudaurelia cytherea cytherea Fabr. (Lepidoptera : Saturniidae) are described.